'It's like a souvenir of something that was important': The role of nostalgic memorabilia in psychological well-being. (1st October 2018) - Masuch, Christoph-Simon; Hefferon, Kate
The identity-establishing powers of actively worn fashion, clothing and dress have been widely explored by fashion scholars. However, the phenomenological aspects of fashion, clothing and dress in general, and the identity-establishing role of retained and treasured yet no longer or only occasionally worn vestimentary objects, have only been marginally explored. Based on data from a constructivist grounded theory analysis on the relationship between well-being and clothing practices, this study expands upon the findings of one particular theme, Eudaimonic Well-Being, and the role of nostalgia and dress memorabilia in identity formation. From semi-structured interviews with ten participants, two additional subthemes were identified: Reminiscing about Past Selves and Preserving Aspects of Self. These themes revealed that dress memorabilia served as aides-memoires and were the storage media of complex, self-relevant information spurring self-reflection. Furthermore, they enabled the positively framed reconsideration of past selves as well as the integration of aspects of past selves into the self-concept. Findings from this study are contextualized and integrated into existing phenomenological works on fashion, clothing and dress. Finally, the concept of dress nostalgia is furthermore developed and future routes for subsequent research are suggested.